Status języka a wola ludu i kodyfikacja. Przypadek śląski - Tambor, Jolanta (Forum Lingwistyczne, 2014)
The status of a language vs. the will of the people and codification. Based on the example of Silesian The article discusses various factors which are perceived as important in discerning linguistic phenomena recognized as languages or dialects. Among the said factors the author mentions the necessity of codification, commenting on the state thereof in relation to the Silesian ethno-language, as well as other linguistic factors. The author states that social issues cannot be omitted, even though establishing the status of a regional language is a legal and political matter. As a vital argument in this discussion, she points at the data collected in the national census from 2011, and particularly at the answer to the questions about one’s national/ethnic identity as well as one’s mother tongue and language used at home. The author also quotes the opinions of the supporters and the opponents of the idea of granting the Silesian ethno-language the status of a regional language. Key words: Silesia, codification, language, dialect, regional language